Chronic gastric anisakiasis provoking a bleeding gastric ulcer - Kang, Dong Baek (The Korean Surgical Society, 2014)
Gastric anisakiasis is a parasitic disease caused by the gastric mucosal penetration of the Anisakis larvae ingested with raw fish. Acute gastric anisakiasis is diagnosed by the endoscopic visualization of Anisakis larvae along with mucosal edema, erythema, hemorrhage, and/or an ulcer, whereas chronic anisakiasis is often observed as a localized tumor commonly occurring in the submucosal layer, and is characterized by eosinophilic granuloma with edema and embedded Anisakis larvae on pathological examination of surgical specimens. We report here a case of chronic gastric anisakiasis provoking a bleeding gastric ulcer, which is a rare clinical manifestation of this condition.